Spinal Intradural Endodermal Cyst Located to the Lumbar Spinal Canal - Akune, Hironobu; Kikuchi, Naoshi; Inokuchi, Takashi; Inoue, Sanshiro; Yokota, Kazuya; Utsunomiya, Takeshi; Miyazaki, Kosei; Takano, Yugo (Orthopedics & Traumatology, 2012)
We describe a very rare case of endodermal cyst of the lumbar spinal canal. A 61-year-old female was admitted with low back pain. MRI exhibited a round-shaped intradural cystic lesion at the L3-4 level. The tumor was completely excised by laminectomy and her symptoms immediately improved. Histopathology confirmed an endodermal cyst. Preoperative diagnosis is very difficult because there are only few specific signs of this tumor. Endodermal cyst should be considered in the differential diagnosis of intradural cystic lesions.